Patterns of Neck Nodal Metastasis from Oral Cavity Carcinoma - Khunteta, Nitin; Makkar, Ayush; Badwal, Jaspreet Singh; Katta, Prakhar; Choudhary, Dinesh; Viswanath, Mohinder; Malhotra, Hemant (South Asian Journal of Cancer, 2022)
Objectives The aim is to study the patterns of lymph node metastasis from various sites in oral cavity cancer and determine the risk factors for metastasis.Materials and Methods It is a prospective observational study. The inclusion criteria were—245 patients of carcinoma buccal mucosa, anterior two-thirds of tongue, hard palate, oral surface of soft palate, floor of mouth, vestibule, and alveolus. The exclusion criteria were—patients who had received preoperative chemotherapy or radiotherapy and patients with recurrent disease.Statistical Methods All data were analyzed using SPSS 18.0 and Graphpad prism 7 software for statistical analysis. Count data have been expressed as percentages (%). The χ2 test was used for univariate analysis of the risk factors of cervical lymph node metastasis. The odds ratio value (with 95% confidence interval) was used to express the risk of cervical lymph node metastasis. p-Value of <0.05 was considered as the difference with statistical significance.Results The most common site involved was buccal mucosa. Patterned lymph node metastasis was seen in 93.5% cases. Skip metastasis was seen in 4.31% cases. Level I b was the most common site of nodal involvement for all primary subsites of oral cavity cancer. The incidence of positive nodes on histopathological analysis was highest in cases of lower alveolus (63.15%), followed by tongue.Conclusion In our study, patterns of lymph node metastasis for oral cavity cancer were comparable to other studies with large number of subjects. The incidence of skip metastasis or aberrant status was low. On multivariate analysis, depth of invasion of tumor, pathologic grade, pathologic T stage, and morphologic type of growth were found to be independent predictors of risk for metastasis.
Keywords: patterns of lymph node metastasis; oral cavity cancer; risk factors for metastasis; regional lymph node; skip metastasis; cervical lymph node